Nereocystis and diatoms, going with the flow - Voon, Sheila (My University, 2012)
The purpose of this experiment was to observe the effect of water flow on fertilization success of Nereocystis gametophytes and growth rates of young sporophytes. My null hypothesis was that there would be no differences between the flows. However, I found that in my experimental setup, benthic diatoms outcompeted the Nereocystis sporophytes and grew over them. I thus analyzed differences in diatom growth under different water flow treatments, and found that there was a clear trend of more diatom chlorophyll and organic biomass in high flow conditions.
Keywords: Nereocystis; bull kelp; diatoms